2002
DOI: 10.1515/zna-2002-0811
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Gallium Phosphate Glasses by High-energy X-ray Diffraction

Abstract: X-ray diffraction experiments are used to obtain short-range order information of gallium phosphate glasses of meta-and pyrophosphate compositions. Parameters of the first-neighbor peaks, such as coordination numbers and distances, are obtained. A strong decrease of the Ga-O coordination number from 6.0 0.2 to 4.6 0.2 upon Ga 2 O 3 addition is found, which is accompanied by a shortening of the Ga-O distances. Only GaO 6 octahedra exist at the metaphosphate composition. Close to the pyrophosphate composition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Ga 2 O 3 can be used as glass former or modifier, depending on the Ga concentration . Holubová et al reported that increasing Ga substitution for Zn in the PG [xGa 2 O 3 –(50‐x)ZnO–50P 2 O 5 ] would result in crystallization of GaPO 4 in the glass matrix .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ga 2 O 3 can be used as glass former or modifier, depending on the Ga concentration . Holubová et al reported that increasing Ga substitution for Zn in the PG [xGa 2 O 3 –(50‐x)ZnO–50P 2 O 5 ] would result in crystallization of GaPO 4 in the glass matrix .…”
Section: Discussionmentioning
confidence: 99%
“…Ga 2 O 3 can be used as glass former or modifier, depending on the Ga concentration. [47][48][49] Holubová et al reported that increasing Ga substitution for Zn in the PG [xGa 2 O 3 -(50-x) ZnO-50P 2 O 5 ] would result in crystallization of GaPO 4 in the glass matrix. 50 Likewise, among the GPGs in this study, the GPG3 with the largest amount of Ga 2 O 3 and smallest amount of CaO tends to crystallize in the glassy matrix (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…XRD PDF data on oxide glasses is highly complimentary to neutron diffraction PDF data since neutrons are more sensitive to the oxygen atoms, often providing a stark contrast in the partial structure factor weighting factors. Phosphate glasses [77][78][79][80][81][82][83][84] represent an important class of polymeric and molecular oxide glasses with similar applications to silicates, such as radioactive waste containment and optical fibers as well as biochemistry. Extensive studies have been carried out by Hoppe and coworkers on phosphates doped with rare-earth ions including; La [77], Ga [78], Fe [79], Pb [80], Zn [81], and Ti [82].…”
Section: Experiments On Glasses and Liquidsmentioning
confidence: 99%
“…Phosphate glasses [77][78][79][80][81][82][83][84] represent an important class of polymeric and molecular oxide glasses with similar applications to silicates, such as radioactive waste containment and optical fibers as well as biochemistry. Extensive studies have been carried out by Hoppe and coworkers on phosphates doped with rare-earth ions including; La [77], Ga [78], Fe [79], Pb [80], Zn [81], and Ti [82]. Hoppe et al [77][78][79][80][81][82] developed a set of rules for network changes upon the addition of modifying atoms to describe the disruption of P-O-P bonding units as a function of P 2 O 3 content.…”
Section: Experiments On Glasses and Liquidsmentioning
confidence: 99%
“…[44] Moreover, both Ce and Ga are multivalent ions which, in contrast to monovalent Ag, strengthen the glass network by increasing connectivity to P─O─ groups. [45][46][47][48][49] The aim of the current study was to investigate both the biological and antibacterial ability of gallium-and cerium-doped PG and to determine how these elements influence the PG structure and behavior. To achieve a balance between strong antibacterial capability provided by Ga and therapeutic properties provided by Ce, a dual doped PG has been proposed anticipating that coaddition of Ga and Ce will enable to study possible synergistic effects in this novel PG.…”
Section: Introductionmentioning
confidence: 99%